Thelephora pacifica (Basidiomycota: Thelephorales), a new species of the tropical forests in the Mexican Pacific coast - Villarruel-Ordaz, J.l.; Maldonado-Bonilla, L.d.; Sánchez-Espinoza, A.c.; Garibay-Orijel, R.; Álvarez-Manjarrez, J. (Phytotaxa, 2024)
Thelephora is a genus of ectomycorrhizal fungi distributed in angiosperm and gymnosperm forests around the world. In this study, we describe Thelephora pacifica, a new species associated with tropical oak forests in Mexico. Phylogenetically, it is the sister group of T. pseudoganbajun from China. Morphologically, it corresponds to T. vialis previously reported in Mexico. Thelephora pacifica has a flabelliform basidiocarp with a hymenophore of grayish-brown color with pinkish tinges contrasting with the yellowish-olive margin. It is distributed in the Pacific forests of Mexico, an area with a high potential for endemism.